Dinamika Komunikasi Internal Dalam Ikatan Mahasiswa Muhammadiyah: Analisis Pola Interaksi dan Tantangan Kultural Organisasi - Syahputri, Nazwa Ayu; Sundari, Salsabila; Putra, Akbar Adrian; Iqbal, Iqbal (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
This study aims to analyze the communication methods within the organization and cultural issues that occur in the Muhammadiyah Student Association (IMM), specifically in the Leadership of the Muhammadiyah Student Association Commissariat (PK IMM) of the Faculty of Social and Political Sciences (FISIP) of the University of Muhammadiyah North Sumatra. This research is important because good communication within the organization helps maintain alignment of goals, strengthen shared identity, and ensure the organization's long-term survival. The study uses a descriptive qualitative approach with data collection methods through observation, in-depth interviews, and document collection. Data were analyzed using data reduction, data presentation, and interpretive conclusion drawing steps. The results show that communication methods in PK IMM FISIP UMSU include active vertical, horizontal, and informal communication, but still face several obstacles, such as low participation of new members, an unorganized information system, and a lack of two-way communication. Cultural challenges that arise include differences in backgrounds, communication styles, and the level of understanding of IMM values that is not evenly distributed among members. The lack of strategies for managing cultural diversity leads to the risk of misunderstanding and reduces organizational effectiveness. The research conclusions emphasize the importance of strengthening participatory communication systems, increasing intercultural understanding, and improving the role of leaders as facilitators of inclusive communication to create more adaptive, harmonious, and sustainable organizations